Harga diri dan perilaku konsumtif dalam pembelian produk secara online - Putri Maskani, Shania Ariffah; Noviekayati, IGAA; Rina, Amherstia Pasca (SUKMA : Jurnal Penelitian Psikologi, 2025)
The development of digital technology has facilitated people's shopping activities, especially through e-commerce platforms such as Shopee, Tokopedia, and TikTok Shop. This convenience has triggered an increase in consumer behavior, particularly among students aged 18–21 who are in the phase of searching for identity and the need for social recognition. One psychological factor believed to play a role in consumer behavior is self-esteem. This study aims to determine the relationship between self-esteem and consumer behavior in online product purchases among students in Surabaya City. This study used a quantitative approach with a correlational design. The subjects were students aged 18–21, and data were collected using a self-esteem scale and a consumer behavior scale. Data analysis was carried out using correlation analysis. The results of the study indicate a relationship between self-esteem and consumer tendencies in online shopping. These findings provide an overview of the role of psychological factors in shaping student consumption patterns and serve as a basis for efforts to develop self-management education and healthy consumption among the younger generation.